Economic Independence Through Decorative Calligraphy (Study of Indonesian Islamic Boarding School Alumni in Riau) - Achmad Ghozali; Artis; Rahman (ITB AAS INDONESIA Surakarta, 2025)
This article describes the experience of Islamic boarding school alumni in an effort to improve their economy through the art of decorative calligraphy in Riau. This is because it is based on the observed social phenomenon, where many alumni of Islamic boarding schools who have decorative calligraphy skills are able to achieve economic independence. This study uses a qualitative descriptive approach by observing and taking data from several Islamic boarding schools in Riau, including the Jabal Nur Siak Islamic Boarding School, the Nawawi Djamil Duri Islamic Boarding School, Bengkalis Regency, and the Al-Hidayah Bantan Bengkalis Islamic Boarding School. Data were obtained through observation, interviews and documentation. Based on the results of the research, economic development for calligraphers in Riau can be done with several things, including writing calligraphy in mosques, invitations, including making calligraphy works from various media and materials such as sterofoam, wood waste, from canvas, and so on and opening a calligraphy course institution. The economic condition of calligraphers in Riau has improved, although the results obtained are different, but they can meet their needs such as continuing their education without the help of parents, building houses and so on.